A Decision Support System for Managing Technical Debt: Towards a Systemic Perspective - Franco, Eduardo; Hirama, Kechi; Armenia, Stefano; Skripnikova, Tatyana; Betzin, Sebastian (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Maintaining a software system in operation requires resources to keep it reasonably bug-free, appropriate for the business needs, and still changeable. However, it is challenging to evaluate resource allocation strategies while considering both current and future needs. This paper presents a decision support system, using technical debt concepts, built based on the system dynamics approach that aims to assist decision-makers in evaluating different maintenance investment strategies. The tool can help evaluate future impacts by simulating possible scenarios, generating knowledge and insights for decision-makers, and helping to communicate them among different stakeholders.